The epidemiology of common mental disorders from age 20 to 50: results from the prospective Zurich cohort Study. (24th March 2015) - Angst, J.; Paksarian, D.; Cui, L.; Merikangas, K. R.; Hengartner, M. P.; Ajdacic-Gross, V.; Rössler, W.
Abstract : Background: There are only a small number of prospective studies that have systematically evaluated standardised diagnostic criteria for mental disorder for more than a decade. The aim of this study is to present the approximated overall and sex-specific cumulative incidence of mental disorder in the Zurich cohort study, a prospective cohort study of 18–19 years olds from the canton of Zurich, Switzerland, who were followed through age 50. Method: A stratified sample of 591 participants were interviewed with the Structured Psychopathological Interview and Rating of the Social Consequences of Psychological Disturbances for Epidemiology, a semi-structured interview that uses a bottom-up approach to assess the past-year presence of 15 psychiatric syndromes. Seven interview waves took place between 1979 and 2008. Approximated cumulative incidence was estimated using Kaplan–Meier methods. Results: Rates of mental disorder were considerably higher than those generally reported in cross-sectional surveys. We found rates ranging from 32.5% for major depressive disorder to 1.2% for Bipolar I disorder. The cumulative probability of experiencing any of the mental disorders assessed by age 50 was 73.9%, the highest reported to date. We also found that rates differed by sex for most disorders, with females generally reporting higher rates of mood, anxiety and phobic disorder, and males reporting higher rates of substance- and alcohol-related disorders. Conclusions: These findings confirm those of other long-term prospective studies that indicate the nearly universal nature of disturbances of emotion and behaviour across the life span. Greater community awareness of the normative nature of these experiences is warranted. An important area of future research is study long-term course and stability to determine who among those with such disturbances suffer from chronic disabling mental disorders. Such longitudinal studies may aid in directing services and intervention efforts where they are most needed.